Do Foreign Institutional Investors Improve Price Efficiency?. (3rd July 2020) - Kacperczyk, Marcin; Sundaresan, Savitar; Wang, Tianyu
Abstract: We study the impact of foreign institutional investors on price efficiency with firm-level international data. Using additions to the MSCI index and the U.S. Jobs and Growth Tax Relief Reconciliation Act as exogenous shocks to foreign ownership, we show that greater foreign ownership increases stock price informativeness, especially in developed economies. This increase arises from new information that foreign investors bring in and displacement of less-informed domestic retail investors. Finally, we show that foreign ownership, particularly from active investors, increases market liquidity, reduces firms' cost of equity, and increases firms' real investment growth.